Effects of forest‐use intensity on vascular epiphyte diversity along an elevational gradient. Issue 1 (7th October 2019) - Guzmán‐Jacob, Valeria; Zotz, Gerhard; Craven, Dylan; Taylor, Amanda; Krömer, Thorsten; Monge‐González, María Leticia; Kreft, Holger
Abstract: Aim: Understanding patterns of tropical plant diversity and their vulnerability to anthropogenic disturbance at different spatial scales remains a great challenge in ecology and conservation. Here, we study how the effects of forest‐use intensity on vascular epiphyte diversity vary along a tropical elevational gradient. Location: 3, 500‐m elevational gradient along the eastern slopes of Cofre de Perote, Mexico. Methods: We studied the effects of forest‐use intensity on alpha, beta and gamma diversity of vascular epiphyte assemblages in old‐growth, degraded and secondary forests at eight study sites at 500‐m intervals along the elevational gradient. At each elevation and in each of the three forest‐use intensity levels, we established five 400‐m 2 plots yielding a total of 120 plots. Results: Interactive effects of elevation and forest‐use intensity strongly impacted local‐scale patterns of vascular epiphyte diversity. Species diversity peaked at 500 as well as 1, 500 m above sea level, which deviates from the previously reported hump‐shaped pattern. In most cases, alpha diversity did not differ significantly among forest‐use intensity levels. However, gamma diversity was always lower in secondary forests compared to old‐growth forests across the entire elevational gradient. Within each elevational belt, beta diversity was dominated by species turnover along the forest‐use intensity gradient in the lowlands and declined with increasing elevation, where community composition became increasingly nested. Along the elevational gradient, the spatial turnover of vascular epiphyte community composition was similar among forest‐use intensity levels. Main conclusions: Our results reveal a strong interaction between forest‐use intensity and elevation, making it difficult to extrapolate findings from one elevational belt to another. Our findings highlight the value of old‐growth forest for epiphyte diversity, but also show that degraded and secondary forests—depending on the elevational belt—may maintain a high species diversity and thus play an important role in conservation planning.